Cognitive distributed computing: a new approach to distributed data centres with self-managing services on commodity hardware. (2016) - Mikkilineni, Rao; Morana, Giovanni
New computing, management and programming models with a novel distributed intelligent managed element (DIME) network architecture are used to provide end-to-end service visibility and control across distributed physical or virtual infrastructure. Resulting decoupling of application and service transaction management from both distributed infrastructure management and virtual machine image movement at run-time (as practised today) enables policy based, secure, service-mobility across physical servers or virtual machines deployed in data centres or public clouds. Using the new architecture we have implemented a web-stack with service self-repair, auto-scaling, live-migration and end-to-end service transaction security independent of server and network security mechanisms. In this paper, we describe auto-scaling, live-migration and performance management of an Apache managed application in operation across physical or virtual servers deployed in data centres or public clouds.